2022
DOI: 10.1039/d2nr04418h
|View full text |Cite
|
Sign up to set email alerts
|

Advances in nanobiotechnology-propelled multidrug resistance circumvention of cancer

Abstract: Multidrug resistance (MDR) is one of the main reasons leading to the failure of tumor chemotherapy and affecting the therapeutic effect. There are two main causes of MDR: The first...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 143 publications
0
9
0
Order By: Relevance
“…(4) To elevate the treatment efficiency, combined or synergistic therapy is usually encouraged. [139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158] Inspired by this, nanozymes can be integrated with immunotherapy, chemotherapy, and other ROS-highlighted therapy to magnify the treatment efficiency. This direction will also arouse more interests, propelling clinical translation especially when imparting these functions into one platform and realizing the all-in-one strategy.…”
Section: Discussionmentioning
confidence: 99%
“…(4) To elevate the treatment efficiency, combined or synergistic therapy is usually encouraged. [139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158] Inspired by this, nanozymes can be integrated with immunotherapy, chemotherapy, and other ROS-highlighted therapy to magnify the treatment efficiency. This direction will also arouse more interests, propelling clinical translation especially when imparting these functions into one platform and realizing the all-in-one strategy.…”
Section: Discussionmentioning
confidence: 99%
“…As a branch, iMWA due to low energy utilization and blood flow-carried heat loss usually results in ITM exacerbation and disables ICB since M2-type macrophage recruitment is encouraged. ,, In this report, generally, the combination between MWA and ICB is dominant. Therefore, ICB only benefits a small portion of patients because most patients suffer from low PD-L1 expression. , Various nanotechnologies for potentiating immune responses have been developed to guide and enhance tumor treatment, , which provided increasing inspiration; e.g., ROS-enriched nanoplatforms vary TME including inflammation tuning , and further enhance antitumor immune responses. , Herein, CAR-T immunotherapy was harnessed to first combine with MWA to address the poor generality of ICB and realize the personalized treatment, wherein the sole CAR-T infiltration in solid tumors was also solved by the intratumorally synthesized in situ Au bioreactor-enhanced microwavegenetics represented by HSP70 up-regulation . The intratumorally synthesized oncolytic Au bioreactors could uniformly disperse heat in the tumor, and concurrently, the gel scaffolds could confine heat in tumor, maximally enlarge EAZ, and suppress iMWA …”
Section: Discussionmentioning
confidence: 99%
“…Chen et al established a summary of the biological processes underlying tumor MDR and nano‐based treatment approaches aimed at reversing MDR. The authors concluded that nanomedicine can serve as a basis for advancing more efficient approaches to combat cancer 65 …”
Section: Nanocarriers To Overcome Mdr In Tumor Microenvironmentmentioning
confidence: 99%